Planning for Drainage Development in Jakarta's Urban Settlements with The Concept of a Healthy City - Chairul Muharis; Arni Utamaningsih (PT. Publikasiku Academic Solution, 2023)
The need for land use in Jakarta can be a factor causing the reduced function of infiltration and water flow, resulting in changes and problems in the drainage system. It is suspected that downstream areas such as Jakarta are unable to accommodate excess water, because there may be problems with the channels or drainage system. For this reason, it is necessary to plan a drainage system (drainage network) so that it can function optimally in accordance with Minimum Service Standards (SPM) to accommodate water flow discharge. which is normal, especially during the rainy season and there are high tides so that you don't experience inundation or flooding. This research aims to plan the construction of drainage that is optimal according to standards in Jakarta in order to raise public awareness of the importance of keeping the environment clean, not throwing garbage in the drainage canals and always keeping the drainage canals clean so that they can drain wastewater from settlements, rainwater and puddles smoothly.